ELEMENTS OF FICTION IN ENGLISH MOVIE - Pipit Rahayu (Universitas Negeri Padang, 2015)
This Paper discusses about the analysis of Elements of Fiction in English movie. In this case, focuses on Plot and setting. Plot is the way in which a story's events are arranged, while setting is where the story takes place somer where and at some time. The English movie used in this paper was